HYPERURICEMIA IN DIABETIC PATIENTS : AN ADDITIONAL RISK FACTOR FOR MICROVASCULAR COMPLICATIONS – A CROSS SECTIONAL OBSERVATIONAL STUDY - Mahto, Binay Kumar; Aditya Prakash; Sanjay Kumar; Rashmi Kumari; Sujit Kumar; Shreya, Shreya; Kushwah , Hotam Singh; Ashish Kumar; Tumram, Akshay Shamrao; Shekhar , Shashank (Student's Journal of Health Research Africa, 2024)
Introduction This study aims to evaluate hyperuricemia as an additional risk factor for the development of microvascular complications in diabetic patients. Methods This study involved a total of 200 diabetic patients, divided into two groups: 100 patients with microvascular complications and 100 without these complications, based on their clinical history and examinations. Serum uric acid (SU) levels were measured in both groups and compared. Results Among the 100 patients with microvascular complications, 48 had hyperuricemia, while 52 showed serum uric acid levels within the normal range. In contrast, of the 100 patients without microvascular complications, only 26 presented with hyperuricemia, yielding a P value of 0.0013, indicating a highly significant result. Among the 38 patients with retinopathy, 20 had hyperuricemia and 18 had serum uric acid levels within the normal range, with a P value of 0.0019. Within the group of 32 patients with neuropathy,10 had hyperuricemia and 22 had serum uric acid levels in the normal range, leading to a P value of 0.181. Finally, among the 48 patients with nephropathy, 32 had hyperuricemia and 16 had serum uric acid levels within the normal range, with a P value of 0.000013. Conclusion Serum Uric acid is elevated in microvascular complication as a whole group when compared to those without microvascular complication group and further hyperuricemia is strongly associated with nephropathy and retinopathy but not neuropathy. Recommendation Correcting hyperuricemia in diabetic patients is vital to overcoming microvascular complications and fostering a path toward improved health and vitality.